Hospital spending and length of hospital stay for mental disorders in Hunan, China - Yanni Xiao; Yu Yu; Ziqi Zhou; Wen Liu; Zhihong Luo; Chuwen Tang; Pengfei Xiao; Shi Wu Wen; Xianxiang Zeng; Weijun Zhong; Minxue Shen (Heliyon, 2023)
Objectives: To describe hospital spending and length of stay for mental disorders in Hunan, China. Methods: We extracted hospital care data for Hunan province from the Chinese National Health Statistics Network Reporting System. Patients with mental disorders (ICD-10 codes: F00 to F99) as the principal diagnosis and hospitalized between January 1, 2017 and December 31, 2019 were included. We retrieved information on age, sex, number of comorbidities, diagnosis, level of hospital, hospital costs, date of admission and discharge, length of stay (LOS), and method of payment of eligible participants. Spending at the provincial level, and spending and LOS at the individual level were described. Quantile regression and linear regression were conducted to investigate factors for hospital cost and LOS for major mental disorders. Results: The 2019 annual spending on mental disorders in Hunan province was 160 million US dollars, and 71.7% was paid by insurance. The annual spending on schizophrenia was 84 million dollars, contributing to a primary burden of mental disorders. The median spending for mental disorders was $1,085 per patient, and the median hospital stay was 22 days. The study identified several significant factors associated with hospital cost and LOS, including age, sex, comorbidity, and level of the hospital. In particular, a higher level of the hospital was associated with a higher hospital spending but a shorter LOS. Women with schizophrenia had a comparable hospital spending but a significantly shorter LOS than men with schizophrenia. Conclusion: Hospitalization spending for patients with mental disorders is substantial. Schizophrenia is the major burden of hospitalization for mental disorders. While patients treated at a higher level of hospital had higher spending, they stayed shorter in these hospitals.